Portal Vein/Aorta Ratio in Dogs with Acquired Portosystemic Collaterals. (14th August 2017) - Sakamoto, Y.; Sakai, M.; Watari, T.
Abstract : Background: The portal vein (PV) diameter increases in humans with portal hypertension (PH). However, there is no evidence of PV enlargement in dogs with PH. Objectives: To measure the PV‐to‐aorta (PV/Ao) ratio in dogs with PH (chronic hepatitis [CH], primary hypoplasia of the PV [PHPV]), in dogs with extrahepatic congenital portosystemic shunt (EH‐CPSS), and in healthy dogs, and to evaluate the relationship between PV/Ao ratio and splenic pulp pressure (SPP). Animals: Twenty‐five dogs with acquired portosystemic collaterals (APSCs; 15 with CH, 10 with PHPV), 32 dogs with EH‐CPSS, and 20 healthy dogs. Methods: Retrospective study. The PV/Ao ratio was calculated with images obtained by computed tomography. SPP was measured at the time of liver biopsy in 45 dogs. Results: Median PV/Ao ratio was similar between dogs with CH (1.35, range 1.05–2.01) and healthy dogs (0.95, 0.80–1.15), but differed significantly between the CH group and both the PHPV (0.40, 0.24–0.67) and EH‐CPSS groups (0.30, 0.11–0.64) ( P < .001). The PV/Ao ratio was significantly lower in the PHPV group than in healthy dogs ( P < .05). It also correlated positively with SPP ( r s = 0.71; P < .001). However, there was no intragroup correlation between SPP and the PV/Ao ratio in any group. Conclusions and Clinical Importance: The PV/Ao ratio can be evaluated in dogs with APSCs on computed tomography. Further studies are needed to examine the relationship between SPP and the PV/Ao ratio in larger groups of dogs with PH and to determine its clinical relevance.